Efficiency of Mobile Network Operators from a Data Service Perspective - Manohar Bayyapu Reddy; Constantine Bielov; Benjamin Finley; Kalevi Kilkki; Hitoshi Mitomo (International Telecommunications Society (ITS), 2019)
The ubiquity of mobile devices such as smartphones, laptops, tablets, and mobile routers drives unprecedented mobile data traffic every year. However, the actual mobile data usage per subscriber or data volume delivered to the subscriber varies significantly between operators and nations. Understanding the reasons behind these differences is important for the mobile network operator's evolving business and telecom regulation in general. Towards this goal, this study analyzes the efficiency of delivering data services (data usage by subscribers) of 94 mobile operators from 28 countries through the method of data envelopment analysis (DEA). The study also provides a case study of the highly efficient but also very dissimilar data service markets of Finland and India. Overall, the results illustrate that many countries have a single highly efficient MNO due to its effort for market share growth (i.e. a disruptive operator). While in other countries all MNOs displayed good efficiency likely due to country level initiatives. Furthermore, majorly economic disparities between countries highly affect the differences in efficiency scores at the country level. The case study between Finland and India shows the causes for differences in mobile data services from the view of regulation policies, spectrum management, market competition and economic disparities.
Keywords: 330; Data envelopment analysis; efficiency; mobile network operator (MNO); data services